2020
DOI: 10.1002/star.202000025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Konjac Glucomannan on Gelatinization, Retrogradation, and Gelling Properties of Frozen Wheat Starch

Abstract: Konjac glucomannan (KGM), a neutral hydrocolloid, is an important food additive used in many European and Asian countries. In this study, the effects of KGM on the gelatinization and retrogradation of frozen wheat starch are investigated. The effect of the addition of KGM on the freeze‐thaw stability and the textural and rheological properties of the starch gel are also examined. It is found that while KGM significantly reduces the pasting temperature, it increases the pasting viscosity, breakdown value, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Meanwhile, the SV values presented a significantly positive relationship with the adhesiveness of noodles. The higher SV values of starches meant the stronger short‐term ageing ability of noodles and greater intermolecular association of leached amylose (Zhou et al ., 2015; Guo et al ., 2021). The molecule activity was limited during the short‐term ageing, due to the strong intermolecular association of starches, especially amylose.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the SV values presented a significantly positive relationship with the adhesiveness of noodles. The higher SV values of starches meant the stronger short‐term ageing ability of noodles and greater intermolecular association of leached amylose (Zhou et al ., 2015; Guo et al ., 2021). The molecule activity was limited during the short‐term ageing, due to the strong intermolecular association of starches, especially amylose.…”
Section: Resultsmentioning
confidence: 99%
“…As an important source of dietary fiber and food raw materials, KGM and its compounds play a certain role in the food field 127 . In addition to KGM playing an important role in the food industry, KGM due to its excellent biocompatibility, good physical properties, such as water absorption and water retention, 128 viscosity, 129 and gelating‐forming ability, 130 therefore, KGM‐based gel has a certain potential in the study of wound dressings 19…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…KGM has high water retention and good swelling, thickening, gelling, emulsifying, suspending, and cohesive properties, and its performance is superior to some gelling agents for food, such as agar, carrageenan, and gelatin. Therefore, it is often used in food processing, beverage preparation and cosmetics [ 7 ]. It is reported that adding KGM to protein such as minced fish, wheat and pork will change their physical and chemical properties and gelling properties.…”
Section: Introductionmentioning
confidence: 99%